Pengaruh Lingkungan Masyarakat Terhadap Civic Responsibility Remaja di Kelurahan Hadimulyo Barat Kecamatan Metro Pusat Kota Metro - Safitri; Adha, Muhammad Mona; Pitoewas, Berchah (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2021)
The country of Indonesia is currently undergoing rapid changes with all its effects. The changes that occur are certainly very influential on the order of life, especially the attitudes and behavior of teenagers as young citizens. The community environment as one of the main factors in shaping the character of teenagers, should be able to support the formation of one of the good characters for teenagers to have, namely civic responsibility. But in reality at this time, the cause of some of the irresponsible behavior carried out by teenagers is from the community around the teenagers themselves. The problem that will be discussed in this study is how the influence of the community environment on civic responsibility. The research method used is descriptive method with a quantitative approach. Data collection techniques used the main technique, namely questionnaires and supporting techniques, namely interviews. The tool to analyze the data in this study is using SPSS version 25. Based on the results of the research conducted, it shows that there is an influence of the community environment on Youth Civic Responsibility in Hadimulyo Barat Village, Metro District, Metro City Center with a large percentage of the influence, namely 59%.